Pengungkapan Risiko Pada Perusahaan Milik Negara (State Owned Enterprise) - Priatnasari, Yeni; Hetika, Hetika; Widianto, Andri (Program Studi Akuntansi, Fakultas Ekonomi dan Bisnis, Universitas Widya Gama, 2020)
ABSTRACT This study examines risk disclosure which is currently a fairly hot discussion among researchers. There are few studies have examined the relationship between mandatory disclosure and corporate voluntary disclosure. In this study, researchers will conduct a descriptive study of mandatory and voluntary disclosure conducted by BUMN in Indonesia. The result of the research shows that the level of mandatory disclosure that should be carried out by SOEs and the level of risk disclosure that is voluntary by BUMN It is hoped that from this research there will be a follow-up in the form of government policies to improve the level of disclosure of BUMN in Indonesia. Kata kunci : State owned enterprises disclosure ; teori institusional; Risk management disclosure; manual content analysis